The Effect of Eight Weeks of Resistance Training on the Record of Young Sprint Runners - Bager ShojaAnzabi; Ebrahim Piri; Reza Farzizadeh (Biyumikānīk-i varzishī)
Objective Resistance training is a fundamental method for inducing muscle growth, enhancing functional capacity, and preventing injuries among athletes. The aim of this study was to investigate the effects of an eight-week resistance training program on the performance progress of young sprint runners. Methods This semi-experimental study involved the selection of 34 young runners who were then randomly assigned to either a training group or a control group. The exercise group underwent resistance training sessions for eight weeks. Parameters including absolute power, relative power, lower limb power, and 100m sprint records were analyzed. The Multivariate Analysis of Variance (MANCOVA) test was employed to compare the pre-test and post-test results of the two groups. Additionally, the correlated t-test was used to compare post-test results between the groups. The paired t-test was also utilized to compare pre-test and post-test results within the training group. All statistical analyses were conducted using SPSS version 26. Results The findings revealed that the exercise group, which underwent resistance exercises with weights for eight weeks, experienced a significant improvement compared to the control group. Furthermore, factors such as absolute strength, relative strength, lower limb strength, and limb telemetry showed significant increases. Additionally, athletes in the training group achieved faster sprint records. Conclusion Resistance training promotes muscle hypertrophy, enhances power, and improves sprint records. Therefore, it can be concluded that athletes involved in track and field events utilize resistance training as part of their preparation to enhance performance and achieve record-breaking results.